2001
DOI: 10.5858/2001-125-0872-ciaopa
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Image Analysis of p53 and Proliferating Cell Nuclear Antigen Expression in Benign, Hyperplastic, and Malignant Endometrium

Abstract: Context.—The endometrium is an intrinsically dynamic tissue with great capability for regeneration and proliferation; consequently, there is some overlap between features seen in benign, premalignant, and malignant lesions. This leads to marked intrabiopsy, interbiopsy, and interobserver variability. Objective.—We studied the specificity and sensitivity of computerized image analysis of molecular markers to evaluate its potential use as a diagnostic tool. Design.—Specimens from 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…In the current study, none of the normal endometrium, simple hyperplasia, and complex hyperplasia without atypia showed any positivity for p53. These negative results were also reported by Elhafey et al, 18 and Sakuragi et al, 19 . P53 immuno positivity was observed in 2 out of 10 cases (20%) of atypical endometrial hyperplasia, Figure (1).…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…In the current study, none of the normal endometrium, simple hyperplasia, and complex hyperplasia without atypia showed any positivity for p53. These negative results were also reported by Elhafey et al, 18 and Sakuragi et al, 19 . P53 immuno positivity was observed in 2 out of 10 cases (20%) of atypical endometrial hyperplasia, Figure (1).…”
Section: Methodssupporting
confidence: 80%
“…P53 immuno positivity was observed in 2 out of 10 cases (20%) of atypical endometrial hyperplasia, Figure (1). Elhafey et al 18 found immuno positivity in 3 of 10 cases (30%) of atypical endometrial hyperplasia, while Sakuragi et al 19 found no p53 immuno positivity in 3 cases (100%) of atypical endometrial hyperplasia. This variability can be explained by the small sample size of atypical endometrial hyperplasia.…”
Section: Methodsmentioning
confidence: 94%
“…23 We were able to confirm that p53 expression is inversely related to that of estrogen and progesterone receptors, thus indicating a dual theory of carcinogenesis in the endometrium. 11,[23][24][25][26] Expression of the markers studied was not significantly associated with the disease stage. It has been reported that p53 expression correlates with more advanced stages.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the use of this type of software, it was possible to evaluate each preparation according to the same criteria. Digital image analysis has already been used in endometrial cancer research [27][28][29]. Besides the evaluation of the receptor expression itself, it is possible to evaluate the surface area, optical density, or the shape of the cell nuclei.…”
Section: Discussionmentioning
confidence: 99%